Analisis Faktor Pengaruh Behavoural Intention Pada Aplikasi Bibit Menggunakan Model UTAUT 2 - Salwa Nabila Nuraeni; Muhammad Bintang Reviandra; Abdul Yusuf (Jurnal Ekonomika dan Bisnis, 2022)
Rapid technological developments do not only focus on aspects of technology itself, but technological developments have affected all aspects of human life. One of these aspects of life is finance. Technology assessment using the Unified Theory of Acceptance and Use of Technology (UTAUT) model can be a good solution. Moreover, it will be efficient to use the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) model which is the evolution of UTAUT. This study was made to analyze the effect of behavior intention on the BIBIT application using the UTAUT 2 model. This analysis was carried out based on an in-depth review of various reliable reference sources. The results can be seen regarding theoretical studies, literature reviews, previous research, results and discussions and conclusions and suggestions.